(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Exploration of rolls hydrodynamic destroys at traumatic visual nerve injurious were not carried out before. Purpose was to refine pathogenic role of eyes hydrodynamic in traumatic optical neuropathy. Material and methods. It was examined 23 of patients (46 eyes) with traumatic optical neuropathy (TON). It was used examination of visual acuity, ophthalmoscopy, perimetry, Humphrey-perimetry, tonography by Nesterov. Results. The study identified four morpho-functional forms TON. Edematous, combined and ischemic forms are stages of development TON, because they have common functional manifestations and hydrodynamic performance. The contralateral normalization of the minute volume of the liquid at 1 month can be considered as a system of self-compensation. In 10 % of cases develop TON has negated character when pathological disorders hydrodynamics of both eyes (increased ease of movement, hypotension, and a decrease in minute volume of fluid) lead to the most severe bilateral lesions of the optic nerve, and therefore require more detailed study. Conclusions. Taking into account the features of hydrodynamics eyes in the diagnosis of traumatic lesions of the optic nerve will allow them to further explore the pathogenic mechanisms and clarify the indications and timing of application of therapeutic measures.